1999
DOI: 10.1007/s100500050286
|View full text |Cite
|
Sign up to set email alerts
|

Kaon squeeze-out in heavy ion reactions

Abstract: The squeeze-out phenomenon of K + and K − mesons, i.e. the azimuthal asymmetry of K + and K − mesons emitted at midrapidity in heavy ion reactions, is investigated for beam energies of 1-2 A.GeV. It is found that the squeeze-out signal is strongly affected by in-medium potentials of these mesons. The repulsive K + -nucleus potential gives rise to a pronounced out-of-plane emission of K + 's at midrapidity. With the K + potential we reproduce well the experimental data of the K + azimuthal distribution. It is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 30 publications
3
31
1
Order By: Relevance
“…First data from KaoS [161] for semi-central Au+Au at 1 AGeV showed a clear squeezeout signal for midrapidity kaons. In corresponding transport calculations from the Texas/Stony Brook group [217,161] and the Tübingen group [179] the data could only be reproduced by the presence of the repulsive K + mean field. Elastic rescattering of K + mesons was found to be too weak to create the observed squeeze-out signal.…”
Section: In-plane Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…First data from KaoS [161] for semi-central Au+Au at 1 AGeV showed a clear squeezeout signal for midrapidity kaons. In corresponding transport calculations from the Texas/Stony Brook group [217,161] and the Tübingen group [179] the data could only be reproduced by the presence of the repulsive K + mean field. Elastic rescattering of K + mesons was found to be too weak to create the observed squeeze-out signal.…”
Section: In-plane Flowmentioning
confidence: 99%
“…The first predictions for K − out-of-plane emission pattern were made by Wang et al [179] and are shown in Fig. 36.…”
Section: In-plane Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…A large fraction of the observed out-of-plane enhancement, in contrast to other 5) with IQMD model calculations [22]. models [23,24,25], is caused by the scattering of K + mesons. The transport code (HSD) [25] in contrast predicts a dominant influence of the potential on the emission pattern of the K + mesons.…”
Section: Energy Spectra and Polar Angle Distributionsmentioning
confidence: 99%
“…The transport code (HSD) [25] in contrast predicts a dominant influence of the potential on the emission pattern of the K + mesons. In the system Au+Au at 1 AGeV where both size and life time of the fireball are larger than in the Ni+Ni case, the effect of the repulsive K + N potential was found to be very important [8,23,24].…”
Section: Energy Spectra and Polar Angle Distributionsmentioning
confidence: 99%